Corporate Effective Tax Rates Model Description and Results from 36 OECD and Non-OECD Countries - Hanappi, Tibor (OECD Taxation Working Papers, 2018)
Variations in the definition of the corporate tax base across countries can have significant impacts on tax liabilities associated with a given investment. An accurate assessment of the effects of corporate tax systems on investment thus needs to build on a consistent methodological framework covering not only statutory tax rates (STRs) but also many provisions affecting the base such as, e.g., fiscal depreciation. The new OECD model described in this paper provides such a framework; building on the theoretical model developed by Devereux and Griffith (1999, 2003) it presents forward-looking effective tax rates (ETRs) for 36 OECD and Selected Partner Economies taking into account a wide range of corporate tax provisions. Empirical results confirm that corporate tax bases vary considerably across countries and asset categories; since tax bases are typically narrower in countries with higher STRs, ETRs tend to be less dispersed across countries than STRs